2014
DOI: 10.2989/20702620.2014.947077
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the diameter distribution of Sal plantations by comparing normal, lognormal and Weibull distributions at Tilagarh Eco-park, Bangladesh

Abstract: For many years foresters have been using statistical probability density functions to describe and characterise stand structure. Predicting the current and future yields of a stand is essential for successful stand and timber management. Implicit prediction of current yield is accomplished by using diameter distribution methods. All diameter distribution yield systems predict the number of trees per unit area by diameter class. In this study, the normal, lognormal and the three-parameter Weibull probability de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This diameter structure is typical of even forest stands with high regeneration capacity (Rollet, 1974). This diameter distribution structure was consistent with the study of Deb et al (2014) that found normal distribution in a Shorea robusta plantation in Bangladesh. It was also consistent with the study of Ribeiro et al (2014) which found the same structure in a plantation of Eremanthus erythropappus.…”
Section: Discussionsupporting
confidence: 91%
“…This diameter structure is typical of even forest stands with high regeneration capacity (Rollet, 1974). This diameter distribution structure was consistent with the study of Deb et al (2014) that found normal distribution in a Shorea robusta plantation in Bangladesh. It was also consistent with the study of Ribeiro et al (2014) which found the same structure in a plantation of Eremanthus erythropappus.…”
Section: Discussionsupporting
confidence: 91%
“…Although Sal is listed as a “least concern” species in the IUCN Red list (IUCN Species Survival Commission, ), recurrent anthropogenic disturbances such as overexploitation, deforestation, and encroachment combined with climate change, are major threats to Sal forests (Kushwaha & Nandy, ). Results from previous work suggest that the natural distribution of Sal has contracted very rapidly over the last few decades, and it is thus highly vulnerable to climate change (Chitale & Behera, ; Deb, Salman, Halim, Chowdhury, & Roy, ; Sarker, Deb, & Halim, ). Garjan is a “critically endangered” (IUCN Species Survival Commission, ) commercially important Dipterocarp tree naturally distributed in the tropical evergreen, semievergreen, and deciduous forests of Bangladesh, India, Myanmar, Thailand, Cambodia, and Vietnam (Ashton, ).…”
Section: Introductionmentioning
confidence: 99%